Amyloid-β and heart failure in Alzheimer’s disease: the new vistas - Al-Kuraishy, Hayder M.; Sulaiman, Ghassan M.; Mohammed, Hamdoon A.; Mohammed, Sohaib G.; Al-Gareeb, Ali I.; Albuhadily, Ali K.; Dawood, Retaj A.; Al Ali, Amer; Abu-Alghayth, Mohammed H. (Frontiers in Medicine, 2025)
Alzheimer’s disease (AD) is the most common cause of dementia and represents 75% of all dementia types. AD neuropathology is due to the progressive deposition of extracellular amyloid-beta (Aβ) peptide and intracellular hyperphosphorylated tau protein. The accumulated Aβ forms amyloid plaques, while the hyperphosphorylated tau protein forms neurofibrillary tangles (NFTs). Both amyloid plaques and NFTs are hallmarks of AD neuropathology. The fundamental mechanism involved in the pathogenesis of AD is still elusive, although Aβ is the more conceivable theory. Aβ-induced neurodegeneration and associated neuroinflammation, oxidative stress, endoplasmic reticulum stress (ER), and mitochondrial dysfunction contribute to the development of cognitive impairment and dementia. Of note, Aβ is not only originated from the brain but also produced peripherally and, via the blood–brain barrier (BBB), can accumulate in the brain and result in the development of AD. It has been shown that cardiometabolic conditions such as obesity, type 2 diabetes (T2D), and heart failure (HF) are regarded as possible risk factors for the development of AD and other types of dementia, such as vascular dementia. HF-induced chronic cerebral hypoperfusion, oxidative stress, and inflammation can induce the development and progression of AD. Interestingly, AD is regarded as a systemic disease that causes systemic inflammation and oxidative stress, which in turn affects peripheral organs, including the heart. Aβ through deranged BBB can be transported into the systemic circulation from the brain and accumulated in the heart, leading to the development of HF. These findings suggest a close relationship between AD and HF. However, the exact mechanism of AD-induced HF is not fully elucidated. Therefore, this review aims to discuss the link between AD and the risk of HF regarding the potential role of Aβ in the pathogenesis of HF.